Risk factors for emergent delivery before 36 weeks among pregnant women with placenta accreta spectrum disorder - Nawaporn Phetrat; Savitree Pranpanus; Thitima Suntharasaj; Chusana Petpichetchian (PLoS ONE, 2025)
Recent studies evaluating risk factors for emergent delivery in women with placenta accreta spectrum disorders have yielded insufficient results. A limited number of studies have evaluated prenatal ultrasound signs of the placenta accreta spectrum as risk factors and have reported inconsistent outcomes. This retrospective study included women with suspected prenatal placenta accreta spectrum who delivered between January 2007 and December 2022 at a tertiary hospital in Southern Thailand. Women who delivered electively or for conditions unrelated to the placenta accreta spectrum before 36 weeks of gestation were excluded. Women who underwent emergent delivery before 36 weeks and delivery after 36 weeks were compared using univariate and multivariable analyses. Overall, 174 women with placenta accreta spectrum were included; 45 (25.0%) underwent emergent delivery before 36 weeks of gestation. Women who delivered before 36 weeks had significantly more premature uterine contractions (41.7% vs. 7.0%, P<0.001), premature rupture of membranes (8.3% vs. 0%, P<0.05), antepartum hemorrhage (75.0% vs. 27.9%, P<0.001), and sonographic findings of placental bulging (45.8% vs. 23.3%, P=0.003) than those who delivered after 36 weeks. The number of premature uterine contractions and antepartum hemorrhage episodes (P<0.001) and more severe placenta accreta spectrum (P=0.003) were significantly associated with emergent delivery. Significant predictors of emergent delivery before 36 weeks were a history of preterm birth (odds ratio: 10.1, 95% confidence interval: 1.0–97.4), presence of premature uterine contractions (9.7, 2.9–31.5), antepartum hemorrhage (6.4, 2.2–18.3), severe placenta accreta spectrum (6.1, 1.5–25.0), and placental bulging (4.4, 1.3–14.2). In conclusion, the significant predictors of emergent delivery before 36 weeks of gestation among women with placenta accreta spectrum were a history of preterm birth, premature uterine contractions or antepartum hemorrhage before 34 weeks, placental bulging, and prenatal diagnosis of severe placenta accreta spectrum.